PENGARUH PELARUT TERT-BUTANOL TERHADAP MINYAK DAN SUHU REAKSI GLISEROLISIS PADA PEMBUATAN MONO DAN DIASILGLISEROL (MDAG) MENGGUNAKAN KATALIS ABU CANGKANG TELUR AYAM - Retno Dian Lestari Purba; Margareth Nainggolan; M. Yusuf Ritonga (Jurnal Teknik Kimia USU, 2014)
Mono and diacylglycerol (MDAG) is one of the synthetic emulsifier agent widely used in food industry. Emulsifier agent is one of the economically high value oleochemical product. The purpose of this research is to produce MDAG through glycerolysis process of refined bleached deodorize palm oil (RBDPO) and glycerol by using egg shell waste as catalyst (4 % of oil weight) for 2 hours, whereas the variables ratio of tert-butanol to oil (1, 2, 3 v/w) and reaction temperatur (60, 70 and 80 oC). Egg shell waste was calcined at 900 oC for 2 hours to form active CaO catalyst. Then glycerolysis process to produce mono and diacylglyserol. Mono and diacylglycerol that formed was separated by using separator fannel. The upper layer was vaporated to separate MDAG from tert-butanol. The content of MDAG was analyzed using Gas Chromatography. The best result was at 70 oC temperature, ratio co-solvent to oil 3:1 (v/w), 2 hours of reaction time and 4% of catalyst amount from oil and oil molar ratio to glycerol 1:6 with MDAG content of 68,62%. MDAG formed are w/o emulsifier with 5.19 HLB. The result of this research shows that egg shell waste is suitable to be used as source of cheap catalyst to produce mono and diacylglycerol.